MEDIATING FOLK MEDIA MESSAGE IN SOCIAL MEDIA: CHALLENGES, ADAPTATIONS, OPPORTUNITIES AND THREATS - R, Rijitha; Gouda, Nikhil Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
During the Covid- 19 pandemic, the production of art and its distribution were severely hit worldwide. The folk forms were the worst affected due to various public gathering restrictions. Challenged by the question of survival, the folk artists experimented with the available resources of art production and distribution. Social media being the most affordable and accessible platform of content distribution came to the rescue of many folk artists who disseminated their performances on social media recorded or live. Inspired largely by David Berlo’s Source-Message-Channel-Receiver (SMCR) model of communication, this paper investigates the challenges faced by the performers and audience during and after the transition and adaptations made in communication, attitude, knowledge; content, elements, structure, treatment, and code to surmount them. In-depth interviews with performers and audiences of this new experimentation were taken for various folk-art forms, e.g., Parai, Street play, and Puppetry of Tamil Nadu. The data were analyzed using the Grounded Theory (interpretative) method both manually and with the help of online software. The findings of the study reveal many noteworthy aspects of traditional media content conceptualization, production, distribution, and audience reception in the digital era with some possible opportunities and threats.